2004
DOI: 10.1128/iai.72.3.1775-1785.2004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Surface-Exposed, Functional Domains of Gonococcal Transferrin-Binding Protein A

Abstract: The gonococcal transferrin receptor is composed of two distinct proteins, TbpA and TbpB. TbpA is a member of the TonB-dependent family of integral outer membrane transporters, while TbpB is lipid modified and thought to be peripherally surface exposed. We previously proposed a hypothetical topology model for gonococcal TbpA that was based upon computer predictions and similarity with other TonB-dependent transporters for which crystal structures have been determined. In the present study, the hemagglutinin epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 52 publications
(69 reference statements)
2
44
0
Order By: Relevance
“…Specificity was demonstrated by reduced binding of the post-immune antisera against a mutant strain that lacks TbpA (Fig.1C). Surface exposure of the L2 epitope was demonstrated in a previous study wherein an HA epitope insertion into the L2 domain was also surface exposed in whole gonococci [35]. We have previously noted that the sequence comprising L2 of TbpA was well conserved among gonococcal strains [12] and in the current study, this observation was extended to include L2 from gonococcal strain MS11 (Fig.…”
Section: Rationale For Selection Of Epitopes For Inclusion In a Chimementioning
confidence: 75%
“…Specificity was demonstrated by reduced binding of the post-immune antisera against a mutant strain that lacks TbpA (Fig.1C). Surface exposure of the L2 epitope was demonstrated in a previous study wherein an HA epitope insertion into the L2 domain was also surface exposed in whole gonococci [35]. We have previously noted that the sequence comprising L2 of TbpA was well conserved among gonococcal strains [12] and in the current study, this observation was extended to include L2 from gonococcal strain MS11 (Fig.…”
Section: Rationale For Selection Of Epitopes For Inclusion In a Chimementioning
confidence: 75%
“…To provide a selectable marker for incorporation of the TbpA L9HA epitope insertion, a new plasmid was constructed. The previously described plasmids pVCU521 and pUNCH755 (16,27) were digested with XbaI. The pUNCH755 fragment containing am mTn3(Cm) cassette was then ligated to pVCU521.…”
Section: Methodsmentioning
confidence: 99%
“…To generate the double mutant MCV858, strain FA19 was used as the recipient strain for transformation with two genetically unlinked markers (encoding TbpA L9HA and TbpB LSAC). Congression was used to provide a selectable marker for gonococcal transformation as previously described (27). Briefly, linearized plasmid DNA encoding the TbpA loop 9 HA epitope insertion and plasmid DNA encoding the TbpB LSAC mutation were added simultaneously as donor DNAs to competent gonococci.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that the TbpA plug domain is important for iron internalization (63); however, the precise mechanism was not defined. We hypothesize that the plug domain of TbpA functions in multiple steps of transferrin-iron uptake.…”
mentioning
confidence: 99%